Arm and leg coordination during breaststroke: Analysis of 9th FINA World SwimmingChampionships, Fukuoka 2001 - Takagi, H.; Sugimoto, S.; Miyashita, M.; Nomura, T.; Wakayoshi, K.; Okuno, K.; Ogita, F.; Ikuta, Y.; Wilson, B. (Biomechanics and Medicine in Swimming IX, 2003)
The purpose of this study was to analyze stroke phases and arm-leg coordination during breaststroke in elite male and female 50, 100 and 200 m events. The swimmers were participants of the preliminary, semifinal and final race in 50, 100 and 200 m breaststroke events in the 9th FINA World Swimming Championships, Fukuoka 2001. The stroke phase and modes of arm and leg coordination were analyzed underwater with two video cameras. The stroke indices (swim velocity, stroke length and stroke rate) were calculated by using images filmed from above the pool. To compare features about the arm-leg coordination and the stroke indices among the events or between the sexes, the data at the approximate 25 m point were adopted. The arm stroke was divided into four phases (stretch, out-sweep, in-sweep and recovery) and leg kick three phase (stretch, kick backward and recovery). The proportion of each phase for total stroke duration and time synchronization of the arm-leg coordination were obtained. RESULTS Mean swimming velocity values were significantly reduced with increased event distance for both male and female. The lower swimming velocity was associated with a lower stroke rate. The stretch phase of the arm stroke and leg kick showed significantly longer duration as the event distance increased. Soares et al. (1999) also observed in national level breaststrokers, a progressive increment of the non-propulsive phase of the arm stroke as event distance increased. We also observed that lower velocities were are accompanied by longer leg-arm transition phases. In conclusion, although the time duration of the stroke cycle was increased as event distance increment, this was due to a proportional increment of nonpropulsive phase, so that a more efficient gliding technique was typical of the longer event.